Analysis of Crack Initiation and Propagation Thresholds of Inclined Cracks under High-Pressure Grouting in Ordovician Limestone - Bin Xu (Energies, 2021)
Control of the grouting pressure within the critical grouting pressure for crack propagation in Ordovician limestone can not only ensure grout penetration length, but also prevent the risk of creating an artificial water channel. Based on the fracture mechanics theory, a formula was proposed to calculate the critical grouting pressure of mixed mode I-II cracks in Ordovician limestone. The necessary conditions for tilted crack opening, the rationality of the existing empirical value of the maximum allowable grouting pressure was investigated based on the mechanical model. The RFPA2D-Flow numerical simulation software was used to evaluate the deduced theory. The research results show that the deduced theoretical calculation formula of the critical grouting pressure agrees with the numerical simulation results; when the mixed mode I-II fracture initiation occurs, the grouting pressure exceeds the perpendicular stress of the overlying rock; the greater the density of the overlying rock mass, the greater the value of grouting pressure for fracture initiation; when the side pressure coefficient was ≥1, crack dip angle increased and the grouting pressure for fracture initiation tended to decrease; and the empirical grouting pressure at the maximum allowable grouting pressure is 2.0–2.5 pw, which will not cause propagation and failure of the existing crack.